Neuromuscular manifestations of wild type transthyretin amyloidosis: a review and single center’s experience - Živković, Sasha A.; Lacomis, David; Soman, Prem (Frontiers in Cardiovascular Medicine, 2024)
Transthyretin amyloidosis (ATTR) is a condition defined by accumulation of insoluble transthyretin amyloid deposits in multiple organs, especially in the peripheral nerve and heart muscle. ATTR may result from transthyretin mutations (variant ATTR or ATTRv) or may occur with normal transthyretin genotype (wild type ATTR or ATTRwt). ATTRwt was previously known as “senile amyloidosis” and causes cardiomyopathy which may lead to heart failure with a preserved ejection fraction, affecting predominantly elderly men. The exact prevalence of ATTRwt in the general population remains unclear, but its occurrence may be underestimated in women. It was observed that a proportion of ATTRwt cardiomyopathy patients may develop slowly progressing neuropathy that is milder and indolent in comparison with typical progressive neuropathy associated with ATTRv. Furthermore, the causality of neuropathy is often uncertain in patients with ATTRwt. Neuropathy symptoms, including distal sensory loss, unsteadiness and (neuropathic) pain are common in elderly patients with multiple potential causes, and as ATTRwt patients are typically older, relatively high prevalence of peripheral neuropathy is expected with frequent comorbidities. Relatively high prevalence of ATTRwt in elderly population contrasts few documented cases of neuropathy caused by ATTRwt, and there is uncertainty whether ATTRwt neuropathy is an infrequent occurrence or a significant manifestation of multisystemic ATTRwt. We review neurologic and musculoskeletal manifestations of ATTRwt and present clinical features of a single center cohort of ATTRwt patients with suspected peripheral neuropathy.